Perpetrators' Resistance, Victims' Defense Mechanisms, and Psychological Consequences of Subjects Victims of Sexual Violence at Schools - Sari, Sari; Munthe, Yesyurun; Veronica, Maria; Simanjuntak, Nova Lady (CV. Edujavare, 2023)
The goal of this research is that the authors are not in the discussion of catcalling, joking, or compliments that lead to sexual harassment, even though they are all part of sexual harassment. In addition, the authors are also not on a case-by-case exploration of sexual harassment. Researchers rather present the diversity of voices of sexual harassment survivors who are traumatized and then dare to rise with a variety of experiences as resistance to trauma. This qualitative research uses data search and analysis techniques through interviews with three research subjects. The results showed that although the victim limped out of the grip of prolonged trauma, over time, the victim managed to rise through parental support and the diversion of positive and profitable activities for the victim. Support and business opportunities become mental treatment to be brave and resistance tools through oneself to be empowered.